Pergulatan Perempuan Kusamba di Sentra Pengelolaan Ikan - Sukiada, I Nyoman; Girindrawardani, Anak Agung Ayu; Rahayu, Ni Wayan Sri (Humanis; Vol 26 No 4 (2022)DO - 10.24843/JH.2022.v26.i04.p05, 2022)
Development in the field of science and technology has resulted in very basic changes, including changes in the perspective between the positions of men and women. The impact of these changes has resulted in more opportunities for women to participate in the public world. The same is true for women in Kusamba Village in the fish management industry. This study uses a qualitative descriptive method by using a purposive sample informant determination technique. While the data collection techniques use observation techniques, in-depth interviews, and documentation. The theory used to analyze the problem is Pierre Bourdieu's generative structural theory and Foucault's knowledge-power relation theory. The results showed that the struggle of women in Kusamba Village in the fish processing center was able to improve the welfare of families and communities. This can be proven by the increasing number of women's savings in the Kusamba Village Credit Institution. The success of women in improving the welfare of their families and communities has not been able to increase the bargaining position of women in politics, both in the family and in the community.